Abnormal changes in neuropsychological function, brain structure and cerebral perfusion in patients with unruptured intracranial aneurysms - Li, Wei; Zhang, Si; Fan, Weijie; Fu, Xiaomei; Zhang, Dong; Wen, Li (Frontiers in Neurology, 2024)
Background Patients with unruptured intracranial aneurysms (UIAs) often experience emotional changes and cognitive impairments. However, the specific mechanisms underlying these impairments are still not fully understood. Methods In the present study, voxel-based morphometry (VBM) and surface-based morphometry (SBM) were employed to investigate structural alterations in 49 patients diagnosed with UIAs compared with 50 healthy controls. Additionally, this study aimed to analyze the correlations among cortical morphological indices, cerebral blood perfusion values and neuropsychological test results. Results Compared with control group, UIA patients exhibited increased gray matter volume in the right anterior orbitofrontal cortex and decreased gray matter volume in the left thalamus pulvinar and hippocampus. Furthermore, the fractal dimension was lower in the right postcentral gyrus and entorhinal cortex. The cerebral perfusion values in the abnormal brain regions demonstrated a downward trend, which was associated with a reduction in gray matter volume in the left thalamus pulvinar and hippocampus, elevated anxiety levels and impaired executive function. Conclusion UIA patients are prone to cognitive impairment and emotional dysregulation, which are accompanied by subtle changes in local gray matter volume and decreases in fractal dimension and cerebral blood flow. These findings provide new insights into the potential mechanisms underlying the cognitive impairment observed in UIA patients.